PENCIPTAAN BUSANA READY TO WEAR DELUXE DENGAN IDE RUMAH ADAT SUKU OSING MENGGUNAKAN TEKNIK REKALATAR TEKSTIL - Novilia, Sheilla; Inty Nahari; Mita Yuniati; Mein Kharnolis (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The creation of deluxe ready to wear ashion inspired by the traditional houses of the Osing tribe with the application of textile rekalatar techniques is driven by promising market potential and the desire to preserve and introduce Osing culture through fashion works. The objectives of creating this work are (1) to describe the concept of deluxe ready to wear fashion design with the idea of ​​the traditional houses of the Osing tribe using textile rekalatar techniques; (2) to describe the process of making clothes through the Practice-led Research method of creating works; (3) to describe the finished clothes; and (4) to publish the results of the fashion works in the dissemination of fashion shows. The method used in the creation of this work is Practice-led Research by Hendriyana (2021). This method supports the process of creating works through integrated practices in four stages, namely pre-design, design, embodiment, and presentation. The results of this creation are three deluxe ready to wear fashion works. The first work is a women's clothing set consisting of an outer and a mini wrap skirt with embroidery and printing applications enriched with decorative stitching. The second work displays women's clothing in the form of a dress decorated with printed motifs with additional decorative stitching accents, combined harmoniously with short pants. The third piece, a men's piece, combines an embroidered jacket and printed trousers with decorative stitching. This creation was presented at the 35th Annual